Deer Frozen Semen Quality in Tris Sucrose and Tris Glucose Extender with Different Glycerol Concentrations - W M. M Nalley; R Handarini; R I Arifiantini; T L Yusuf; B Purwantara; G Semiadi (Media Peternakan, 2011)
In order to improve Timor deer (Cervus timorensis) frozen semen quality, the influence of sugar and glycerol concentration on semen characteristics of sperm was investigated.  The semen was collected from five sexually mature Timor deer using an electroejaculator. The semen was evaluated and divided into six equal tubes and diluted with Tris sucrose glycerol 10% (TSG10); Tris sucrose glycerol 12% (TSG12); Tris sucrose glycerol 14% (TSG14); Tris glucose glycerol 10% (TGG10); Tris glucose glycerol 12% (TGG12); and Tris glucose glycerol 14% (TGG14). The diluted semen was packed in 0.3 ml minitub straw, equilibrated at 5 oC for 4 hours and frozen on liquid nitrogen vapor for 10 minutes. The total of forward motility, viability, acrosome integrity and membrane integrity were assessed in fresh, after equilibration and after thawing. Results demonstrated that the percentage of sperm motility in TSG10was higher (P (63.93±7.23%). The sperm in TSG10 and TSG14  extender were superior in acrosome as well as in membrane integrity. It was concluded that Tris Sucrose with 10% glycerol protected Timor deer sperm better than other combinations.